Flow boiling data of R452A. (August 2018) - Lillo, Gianluca; Mastrullo, Rita; Mauro, Alfonso W.; Viscito, Luca
Abstract: Flow boiling pressure drop and heat transfer performance of R452A in horizontal single tubes have not been investigated or reported yet in scientific literature. In this paper, local heat transfer coefficient and pressure gradient for R452A are experimentally investigated. Tests have been carried-out in a 6.0 mm internal diameter single horizontal stainless-steel tube from the onset of boiling up to the dry-out conditions at 25°C as average saturation temperature. Mass flux values of 150 and 400 kg/m 2 s and heat fluxes equal to 10 and 20kW/m 2 are considered for the experimental analysis.